Differential extracellular enzymes expression by three Paenibacillus strains using gel-free proteomics análisis - Di Marco, Enzo (2017)
Three Paenibacillus strains, identified according to their 16S rDNA gene sequence and named as AR247, AR460-1 AR489, were selecteddue to their ability to produce glycoside hydrolases (GH) for second generation ethanol and other biotechnological applications. Theassessment of extracellular enzyme production was previously approached by utilizing a mineral-based medium, MM0.2, added withagricultural by-products. These substrates are low-cost and abundantly available carbon sources for biotechnological purposes. Among thetested carbon sources, an alkali pretreated sugarcane bagasse (OH-SCB) was the one that better promoted the production of extracellularxylanases for all strains. The aim of this work was to study the differential extracellular enzymes expression by these strains through gelfree proteomic analysis method.Firstly, crude extracts were obtained by centrifugation after 72 h of cultivation in MM0.2 - OH-SCB 1% medium. Then, samples wereconcentrated by lyophilization and digested by using trypsin for further mass spectrometry analysis. Tryptic peptides obtained wereanalyzed using 2D nano-Ultra Performance Liquid Chromatography, coupled to tandem mass spectrometry . Bioinformatics analysis forprotein identification was performed by searching against Swiss-Prot database, using Mascot server and ProteoIQ v2.8.Peptide summary report provided by Mascot evidenced hemicellulases which are active not only over β-1,4-linkages of xylose unitsbut also on substituents of xylan. An endo-β-1,4-xylanase with 20.1 kDa molecular weight and 9.2 isoelectric point (pI) was foundexclusively in crude extract samples of strain AR247. This enzyme, identified as a GH11, was also detected as a band between 18-20kDa in zymograms and showed a pairwise similarity of ≥ 99 with an homologous from Paenibacillus sp. Y412MC10. In addition, asecond β-1,4-xylanase was identified in the secretome samples, yet not detectable through zymography, from both AR247 and AR489strains. It was of 140.9 kDa, 4.7 pI (potential GH10), and showed to be closely related to a β-1,4-xylanase from P. glucanolyticus.Moreover, additional extracellular xylanase were found, which were related to a GH30 detected in P. favisporus and to two GH25 fromP. polymyxa. Other proteins related to xylan utilization identified were: S?layer protein; sugar ABC transporters and sequences fromsubstrate-binding proteins towards beta glucans. On the other hand, strains AR460-1 and AR489, revealed sequences correspondingto a carbohydrate binding module type CBM54 and an ABC transporter protein. Finally, a chitosanase belonging to GH8 family wasonly found in strain AR489.In conclusion gel-free proteomics analysis proved to be a useful methodology to achieve a widespread knowledge of the enzymaticrepetory contributing to better quality and quantity of results.